Book sharing and reminiscing: caregivers’ conversational style and children's language and literacy development in low-income Costa Rican families - Carmiol Barboza, Ana María (2022)
Parent-child book sharing and reminiscing conversations are two important home activities that promote young children’s early language and literacy skills. Yet extant research has focused on middle-class Anglo-European families, with relatively little attention given to styles of book sharing and reminiscing in other cultural contexts. To further explore home practices and children’s development in Latin America, we examined the relationships between caregiver’s conversational style while reminiscing and book sharing and children’s emerging language and literacy skills. The sample included 108 low-income, Costa Rican caregivers and their preschool-aged children. Results from cluster analyses identified two types of caregiver book sharing styles, the story builder and the storyteller; and two types of reminiscing styles, the high elicitor and the low elicitor. These styles uncovered different links to child participation in conversation and emerging language and literacy skills. Findings are discussed in light of furthering culturally appropriate research, practices, and policy to support early childhood and family literacy for young children and their caregivers in Costa Rica.